Contribution of the dihydropyrimidinase-like proteins family in synaptic physiology and in neurodevelopmental disorders - Desprez, Florence; Ung, Dévina C.; Vourc’h, Patrick; Jeanne, Médéric; Laumonnier, Frédéric (Frontiers in Neuroscience, 2023)
The Dihydropyrimidinase‐like (DPYSL) proteins, also designated as the Collapsin response mediators proteins, constitute a family of five cytosolic phosphoproteins abundantly expressed in the developing nervous system but down-regulated in the adult mouse brain. The DPYSL proteins were initially identified as effectors of semaphorin 3A (Sema3A) signaling and consequently involved in regulation of growth cone collapse in young developing neurons. To date, it has been established that DPYSL proteins mediate signals for numerous intracellular/extracellular pathways and play major roles in variety of cellular process including cell migration, neurite extension, axonal guidance, dendritic spine development and synaptic plasticity through their phosphorylation status. The roles of DPYSL proteins at early stages of brain development have been described in the past years, particularly for DPYSL2 and DPYSL5 proteins. The recent characterization of pathogenic genetic variants in DPYSL2 and in DPYSL5 human genes associated with intellectual disability and brain malformations, such as agenesis of the corpus callosum and cerebellar dysplasia, highlighted the pivotal role of these actors in the fundamental processes of brain formation and organization. In this review, we sought to establish a detailed update on the knowledge regarding the functions of DPYSL genes and proteins in brain and to highlight their involvement in synaptic processing in later stages of neurodevelopment, as well as their particular contribution in human neurodevelopmental disorders, such as autism spectrum disorders and intellectual disability.